2014
DOI: 10.1590/1981-6723.4814
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento das distribuições de temperatura em leito de arroz com casca durante o tratamento térmico por micro-ondas

Abstract: ResumoDurante o aquecimento dielétrico, a distribuição do campo elétrico dentro de uma cavidade ocorre a partir de uma propagação multimodal, ocasionada por inúmeras refl exões das micro-ondas provenientes das paredes metálicas da cavidade. Essas refl exões múltiplas geram regiões de maior e menor intensidade de campo elétrico no espaço e, por consequência, um aquecimento não uniforme no produto. O objetivo deste estudo foi o levantamento dos valores de temperaturas obtidos durante o tratamento térmico por mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…A literature review has shown that several studies have been conducted on microwave drying. The studies are related to the production of husked cherry coffee (Cunha, Canto, & Marsaioli, 2003), coconut husk (Valadez-Carmona, Cortez-García, Plazola-Jacinto, Necoechea-Mondrágon, & Ortiz-Moreno, 2016), dried carrots (Béttega et al, 2014), strawberries (Böhm, Kühnert, Rohm, & Scholze, 2006), macadamia nuts (Silva, Maximo, Marsaioli, & Silva, 2007), and granulated solids (Berteli, Nogueira, & Marsaioli, 2015). However, there is a lack of studies on the microwave drying of Araucaria seeds.…”
Section: Phenolicmentioning
confidence: 99%
“…A literature review has shown that several studies have been conducted on microwave drying. The studies are related to the production of husked cherry coffee (Cunha, Canto, & Marsaioli, 2003), coconut husk (Valadez-Carmona, Cortez-García, Plazola-Jacinto, Necoechea-Mondrágon, & Ortiz-Moreno, 2016), dried carrots (Béttega et al, 2014), strawberries (Böhm, Kühnert, Rohm, & Scholze, 2006), macadamia nuts (Silva, Maximo, Marsaioli, & Silva, 2007), and granulated solids (Berteli, Nogueira, & Marsaioli, 2015). However, there is a lack of studies on the microwave drying of Araucaria seeds.…”
Section: Phenolicmentioning
confidence: 99%